2019
DOI: 10.1021/acsphotonics.9b00184
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Complete Photonic Bandgap in Low Refractive Index Contrast Inverse Rod-Connected Diamond Structured Chalcogenides

Abstract: Three-dimensional complete photonic bandgap materials or photonic crystals block light propagation in all directions. The rod-connected diamond structure exhibits the largest photonic bandgap known to date and supports a complete bandgap for the lowest refractive index contrast ratio down to n high /n low ∼ 1.9. We confirm this threshold by measuring a complete photonic bandgap in the infrared region in Sn-S-O (n ∼ 1.9) 1 arXiv:1905.00404v1 [physics.optics] 1 May 2019 and Ge-Sb-S-O (n ∼ 2) inverse rod-connecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In this and previous works, we have focused our research on 3D photonic crystals, where we have shown partial photonic bandgaps (PBGs) in polymer photonic crystals that were fabricated using direct laser writing, exploiting two-photon polymerization (2PP)-based 3D lithography [11]. More recently, by backfilling polymer crystals with higher-index chalcogenide materials, a complete PBG has been demonstrated in technologically relevant wavelength regions (1.4-1.6 µm) [12]. This direct-writing templating technique is ideal for fabricating arbitrary 3D structures and could allow the selective writing of defects containing fluorescent material at the antinodes of cavities, i.e., the infiltration of the structure with liquid-containing quantum emitters, such as PbS colloidal quantum dots [13], single-walled carbon nanotubes (CNTs) [14], or coating with 2D materials [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In this and previous works, we have focused our research on 3D photonic crystals, where we have shown partial photonic bandgaps (PBGs) in polymer photonic crystals that were fabricated using direct laser writing, exploiting two-photon polymerization (2PP)-based 3D lithography [11]. More recently, by backfilling polymer crystals with higher-index chalcogenide materials, a complete PBG has been demonstrated in technologically relevant wavelength regions (1.4-1.6 µm) [12]. This direct-writing templating technique is ideal for fabricating arbitrary 3D structures and could allow the selective writing of defects containing fluorescent material at the antinodes of cavities, i.e., the infiltration of the structure with liquid-containing quantum emitters, such as PbS colloidal quantum dots [13], single-walled carbon nanotubes (CNTs) [14], or coating with 2D materials [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In this publication, we define the RI contrast as the ratio of the refractive indices of two constituent media, n 1 / n 2 , where n 1 is larger than n 2 , so that the minimal contrast is 1. To increase the range of available materials for PBG applications, there have been considerable efforts to minimize the required RI contrast employing periodic [ 4,22–26 ] and aperiodic [ 21,27–35 ] structures. As aperiodic structures are not limited by the crystallographic theorem and thus are allowed for a more flexible positioning of Bragg peaks and smoother effective Brillouin zones, they are generally considered superior for low‐contrast CPBGs.…”
Section: Introductionmentioning
confidence: 99%
“…The technique, which made use of pulsed lasers within the picosecond or femtosecond regime, was capable of defining any 3D geometry within a polymer, at a resolution of order 100 nm. From the 2000s onwards it has been used to great effect in order to realise photonic crystals [22][23][24][25][26], microfluidic channels [27] and cell scaffolds [28][29][30][31]. It would be another 15 years before the potential of two-photon lithography was exploited to realise 3D magnetic nanostructures.…”
Section: Introductionmentioning
confidence: 99%